HISTOPATHOLOGICAL AND HISTOCHEMICAL CHANGES IN THE IUNG OF GUINEA PIGS EXPERIMENTALLY INFECTED WITH NOCARDIA ASTEROIDES ’ - ALWAN, M J; ALKAISIE , B I; ABDUL RAHMAN, R A (The Iraqi Journal of Veterinary Medicine, 2022)
The pathological and histochemical changes inthe lung of ten guinea pigs have been investigated after using viable Nocardia asteroides in a dose of 1.5*108 cfc, thebacteria was injected intrapulmonary. Lesions of pyogranuloma were developed. Histochemical studies showed that the granules of goblet cells and mucos glands of lung contain a mixture of neutral and sialomucin normal animal , these types of mucin changed to sialomucin and sulfomucin inthe infected animals.